2008
DOI: 10.1055/s-2007-995550
|View full text |Cite
|
Sign up to set email alerts
|

Früherkennung von Hörstörungen

Abstract: Schlüsselwörter l " UNGHS l " Hörstörungen l " Follow-up l " Tracking l " Screening Bibliografie

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…Recently, the prelingual development of congenitally deaf children has become an area of particular interest (Moeller, 2007). Newborn Hearing Screening (NHS) allows early identification of children with hearing impairment and provides an opportunity for cochlear implantation to be performed in appropriate candidates at a very young age (Schade, 2008). Clinically, there is a need for valid diagnostic tests to accurately assess the prelingual speech development of infants and toddlers with hearing impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the prelingual development of congenitally deaf children has become an area of particular interest (Moeller, 2007). Newborn Hearing Screening (NHS) allows early identification of children with hearing impairment and provides an opportunity for cochlear implantation to be performed in appropriate candidates at a very young age (Schade, 2008). Clinically, there is a need for valid diagnostic tests to accurately assess the prelingual speech development of infants and toddlers with hearing impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Zur Verbesserung der Früherkennung kindlicher Hörstörungen haben seit ca. 2000 viele Wissenschaftler unterschiedlicher Fachgebiete ein universelles Hörscreening gefordert [ 5 ] . Der Gemeinsame Bundesausschuss (G-BA) hat 2009 die Einführung des Neugeborenen Hörscreenings (UNHS) beschlossen [ 6 ] .…”
unclassified
“…Many studies have shown that newborn hearing screening without tracking parents up to the initiation of treatment does not significantly advance the time of treatment and newborn hearing screening remains ineffective for many affected children [ 5 ]. Therefore, in addition to the implementation of quality-assured newborn hearing screening, it is essential that children be tracked by a higher screening center at least until the diagnosis is established, possibly even longer [ 6 ]. However, the funding of both the implementation of the screening test as well as the tracking is not regulated in the decision of the G-BA.…”
Section: Newborn Hearing Screeningmentioning
confidence: 99%